Impact of Sample Delay on Leukocyte and Platelet Parameters in Dengue Fever Patients: A Hematological Analysis - Luh Mitha Ari Utami; Heri Setiyo Bekti; I Gusti Ayu Sri Dhyanaputri (Borneo Scientific Publishing, 2024)
Background: The diagnosis of Dengue Fever (DF) involves physical examination, laboratory tests, and confirmation primarily through thrombocytopenia and leukocyte abnormalities. Laboratory procedures play a crucial role; however, delays in complete blood count (CBC) analysis may influence hematological parameters, potentially affecting diagnostic accuracy. Objective: To determine the effect of 2-hour and 4-hour delays in CBC testing on leukocyte and platelet counts in patients with Dengue Fever. Methods: This experimental study used a posttest-only control group design with purposive sampling. Blood samples from DF patients were divided into three groups: immediate testing, 2-hour delay, and 4-hour delay. Data were analyzed using the Shapiro-Wilk test followed by Multivariate Analysis of Variance (MANOVA). Results: The mean leukocyte and platelet counts in the immediate testing group were 4.86×10³/μL and 61.55×10³/μL, respectively. In the 2-hour delay group, leukocyte counts slightly decreased to 4.79×10³/μL and platelet counts increased to 65.77×10³/μL. In the 4-hour delay group, leukocyte counts increased to 4.85×10³/μL while platelet counts decreased to 64×10³/μL. MANOVA results (Sig. = 1.000) indicated no significant differences among the groups. Conclusion: Delays of 2 and 4 hours in CBC testing did not significantly affect leukocyte and platelet counts in Dengue Fever patients. These findings suggest that short-term delays in sample analysis may not compromise hematological results in DF diagnosis.